Teachers' Pedagogical Competence and Students’ Qur’anic Memorization Achievement: Evidence from an Islamic Tahfidz Senior High School - Muhammad Silahudin Ramadani; Fathur Rohman (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine how teachers’ pedagogical competence influences students’ achievement in Qur’anic memorization (tahfidz) in an Islamic senior high school. Education in Islamic contexts is expected to develop intellectual capacity alongside moral and spiritual integrity, yet learning outcomes in intensive tahfidz programs often vary despite similar institutional settings. Previous studies highlight the importance of teacher competence but provide limited empirical insight into pedagogical practices within Qur’anic memorization education. This research employed a qualitative descriptive design and employed observations, in-depth interviews, and document analysis. Data were analyzed using an interactive model that involved reduction, display, and verification. The findings reveal that teachers’ pedagogical competence operates as an integrative instructional framework encompassing learner diagnosis, mastery of learning theories, curriculum development, educative implementation, effective communication, and continuous assessment. Pedagogical competence significantly enhances students’ cognitive accuracy, affective attachment to the Qur’an, and psychomotor precision in recitation. Supportive factors such as qualified teachers, a Qur’anic learning environment, and family support strengthen these outcomes, while weak intrinsic motivation and unstable spiritual intention inhibit learning consistency. This study contributes to Islamic education scholarship by contextualizing pedagogical competence within tahfidz learning and recommends integrating pedagogical training with spiritual mentoring to achieve sustainable memorization outcomes.